IDENTIFIKASI STILISTIKA PADA ASPEK BUNYI IRAMA DALAM WAWANCAN/PUISI LAMPUNG "BANYU/ WAY" KARYA SUKU ABUNG - Nadila Ayu Putri (Wiyata Budaya: Jurnal Pendidikan Dalam Konteks Humaniora, 2025)
Stylistics is intended to explain something that exists in the world of literature and to explain the artistic function, the function of beauty, in other words, stylistics explains the function of beauty in the use of language forms in poetry. Rhythm is the regular alternation of length, short, ups and downs and loudness and softness of spoken sounds. Data collection on aspects of sound. In poetry, it is not only to obtain a poetic effect in the form of poetry, but also to have other effects, for example the effect of beauty in the form of rhythmic sound, orchestration, melody. Apart from rhyming, the arrangement of words in a line of poetry can create a melodic, rhythmic sound and that will make the poem more beautiful, like a song. The aim of this research is to find out the sound aspect of the rhythm in the poem "BANYU/ WAY" by SUKU ABUNG. The data collection method uses the literature review method as a first step in preparing a research framework in order to obtain similar information through books, journals, literature or magazines. Results of this research Poetry can attract a lot of interest from readers and listeners, not only to see, read and hear, but also to interpret the contents of the poetry. Stilistika dimaksudkan untuk menerangkan sesuatu yang ada didalam dunia kesastraan dan untuk menerangkan fungsi arsitik, fungsi keindahan dengan kata lain stilistika menjelaskan fungsi keindahan dalam penggunaan bentuk bahasa dalam puisi .Irama merupakan pergantian panjang pendek, turun naik dan keras lembutnya ucapan bunyi secara teratur Pendataan aspek bunyi pada puisi tidak hanya untuk memperoleh efek kepuitisan yang berwujud persajakan saja, tetapi mempunyai efek efek lain contohnya efek keindahan berwujud keritmisan bunyi,orkestrasi,melodius. Selain bersajak, susunan kata didalam larik puisi itu dapat membuat suara yang melodis, ritmis dan itu akan membuat puisi menjadi lebih indah seperti nyanyian. Tujuan penelitian ini adalah untuk mengetahui bagaimana aspek bunyi pada irama dalam puisi "BANYU/ WAY" karya SUKU ABUNG. Metode pengumpulan data menggunakan metode kajian kepustakaan untuk sebagai langkah awal menyiapkan kerangka penelitian agar memperoleh informasi yang sejenis melalui buku,jurnal ,literatul atau majalah. Hasil dari penelitian ini puisi dapat menarik banyak minat para pembaca serta pendengar bukan hanya sekedar untuk melihat,membaca dan mendengar saja tapi ingin mengartikan isi dari puisinya.